Correlation of morphological and functional indicators with sports results among qualified athletes specializing in freestyle swimming at distances of various lengths - Olga Pilipko; Alina Pilipko (Kharkiv State Academy of Physical Culture, 2019)
Purpose: determine the degree of correlation between morphological and functional indicators and athletic performance among qualified athletes specializing in freestyle swimming at distances of various lengths. Material & Methods: analysis of literary sources, timekeeping, anthropometric and physiological measurements, methods of mathematical statistics. The contingent of the examined was composed of qualified athletes specializing in freestyle swimming at sprint, middle and stayer distances. Results: the authors formed a morphological and functional profile of qualified athletes specializing in freestyle swimming at distances of various lengths, studied the differences that occur in indicators of the level of morpho-functional development of athletes depending on their distance specialization, determined the degree of correlation between morpho-functional performance and sport result among qualified swimmers specializing in sprinting, middle and stayer distances. Conclusions: determining the degree of relationship between morphological and functional indicators and sports results at different distances in freestyle can be used to improve the selection and orientation of qualified swimmers.